International Lessons for African Higher Education and Economy - Pillay, Pundy (International Higher Education, 2011)
This article distils some important lessons for Sub-Saharan Africa using case studies of three systems which have successfully linked their economic development and higher education policy and planning: namely Finland, South Korea, and North Carolina state in the USA. These lessons include the link between economic and education planning; the need for a high quality schooling system as the foundation for a productive higher education system; the importance of institutional differentiation, and the role of the state. Finally, it suggests reasons why policy makers should take note of the importance of higher education for development generally, and for economic development specifically.